2023
DOI: 10.1002/ana.26679
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 Induces Neuroinflammation and Suppresses Peroxisomes in the Brain

Abstract: ObjectivePeroxisome injury occurs in the central nervous system (CNS) during multiple virus infections that result in neurological disabilities. We investigated host neuroimmune responses and peroxisome biogenesis factors during severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection using a multiplatform strategy.MethodsBrain tissues from coronavirus disease 2019 (COVID‐19) (n = 12) and other disease control (ODC) (n = 12) patients, as well as primary human neural cells and Syrian hamsters, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…Indeed, neuroinflammation has been reported in COVID-19 patients, especially in those requiring hospital or intensive care unit treatment. Interestingly, several inflammatory mediators such as TNF-α, IL-1β, NF-κB, IL-6, and MHCII, along with Iba-1 and GFAP-positive cells, are AD biomarkers and are activated in COVID-19 ( 61–64 ). This suggests a possible common mechanism leading to the increasing risk of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, neuroinflammation has been reported in COVID-19 patients, especially in those requiring hospital or intensive care unit treatment. Interestingly, several inflammatory mediators such as TNF-α, IL-1β, NF-κB, IL-6, and MHCII, along with Iba-1 and GFAP-positive cells, are AD biomarkers and are activated in COVID-19 ( 61–64 ). This suggests a possible common mechanism leading to the increasing risk of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotropism of SARS-CoV-2 is still under debate. Several in vitro studies showed that the cells of the CNS, particularly astrocytes and neurons, support SARS-CoV-2 replication ( Bullen et al, 2020 ; Jacob et al, 2020 ; Ramani et al, 2020 ; Wang et al, 2021 ; Andrews et al, 2022 ; Crunfli et al, 2022 ; Roczkowsky et al, 2023 ). In contrast, viral RNA was either absent ( Khan et al, 2021 ; Lee et al, 2021 , 2022 ; Yang et al, 2021 ) or present in low levels in a subset of the autopsy brain samples from fatal COVID-19 patients ( Kantonen et al, 2020 ; Matschke et al, 2020 ; Puelles et al, 2020 ; Solomon et al, 2020 ; Meinhardt et al, 2021 ; Roczkowsky et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Omicron and its successor variants can infiltrate the CNS through the olfactory bulb, they not only induce inflam-mation in neurons, microglial cells, and astrocytes but can also directly damage neuronal cells. [22][23][24][25][26] Indeed, the direct infection of neuronal cells has been highly recognized as a significant factor contributing to neurological complications associated with COVID-19. 27,28 Over time, an increasing number of novel variants, such as XBB and JN.1, continue to emerge, leading to a growing interconnectedness between the virus and human existence.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging SARS‐CoV‐2 variants, particularly Omicron and its successors, demonstrate altered virological characteristics, notably an increased inclination for neurotropism and neurotoxicity compared with earlier strains 20,21 . Omicron and its successor variants can infiltrate the CNS through the olfactory bulb, they not only induce inflammation in neurons, microglial cells, and astrocytes but can also directly damage neuronal cells 22–26 . Indeed, the direct infection of neuronal cells has been highly recognized as a significant factor contributing to neurological complications associated with COVID‐19 27,28 .…”
Section: Introductionmentioning
confidence: 99%